Social media and migrants’ perceptions: Portugal as a potential host country for Brazilian workers - Flávio Nunes (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Social media use is increasingly affecting the various stages preceding the decision to emigrate, including the selection of final destination. Future migrants meaningfully use ICT to connect with those workers who are already living abroad, as a result more accurate perceptions of host societies are emerging through peers’ experiences. This study evaluates the specific role played by YouTube in the way Brazilians are creating their mental images of Portugal. A sample of 135 YouTube videos were analyzed, in which Brazilian emigrants share their testimonies of adaptation to the Portuguese reality. The conclusions point out to a mismatch between the low skills’ jobs, locally available in the Portuguese labor market, and the higher qualification profile of many Brazilian workers who moved to Portugal. If expectations must be reduced in terms of economic prosperity, there is a consensus regarding a higher quality of life, in a broader sense, experienced by Brazilian migrants after their decision to live and work in Portugal.